Individualised care and related concepts - Papastavrou, Evridiki (My University, 2019)
The aim of this chapter is to describe and analyse significant evidence of individualised care as related to other concepts, such as care and caring behaviours, patient participation in care, patient satisfaction, nurse satisfaction, patient autonomy, patient empowerment and quality of life. This chapter is based mainly on the results of two international research projects (Care and Individualised Care Projects) that have explored individualised care in relation with caring behaviours and patient satisfaction. Patients were asked to give their own opinion of what they mean by individualised care as well as their experience about the care they received, whether they felt that it was actually individualised according to their own needs and preferences. The results provided evidence that patients and nurses have different perceptions of individualised care, suggesting that both patients’ and nurses’ evaluations are needed to deliver care according to each individual patient’s needs, experiences, behaviours, feelings and perceptions. Other relations are also discussed through smaller-scale studies performed in different countries which underline the internationality and the challenges of exploring the individualised care concept. This chapter could provide useful information to nursing managers and policymakers on introducing nursing approaches and practices based on individualised care so as to improve quality of care, enhance patient dignity, keep people safe and consequently increase patients’ satisfaction.
Keywords: Caring behaviour; Ethical issues; Individualised care; Participation; Satisfaction